Penafsiran Modern Ayat-Ayat Waris: Perbandingan Muḥammad Shaḥrūr dan Munawir Sjadzali - Muhammad Iqbal Piliang; M. Najib Tsauri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2019)
This paper discusses inheritance discourse based on verses of the Qur’an according to modern interpreters, Muḥammad Shaḥrūr with Munawir Sjadzali. Both interpreters are appointed because they can be considered to have tried in their respective contexts to answer the emergence of ambiguous attitudes in implementing inheritance law from Muslim societies. Muḥammad Shaḥrūr understands and applies it in a way that is different from the opinions and concepts, as seen in the 'four classical patterns of calculation' (al-amalīyāt al-arba 'fī al-ḥisāb) as well as in social aspects, such as the concept of patrilinialism in society and the spirit of kinship and family spirit and ethnicity which became the benchmark for the distribution of inheritance in the past century or in political aspects, such as overlapping concepts of inheritance law which confuse ownership, law and prophetic authority. From this there is a clear relevance between the boundary theory proposed by Shaḥrūr and the efforts to reform Islamic law which are expected to grow with justice and be able to answer the needs of the community. Whereas Sjadzali developed the concept of inheritance contained in the Qur'an, to look for the relevance of Islamic teachings to the times, especially in the context of Modern Indonesia. Since al-Qur'an is multidimensional, as hudan li al-nās, the concept of Sjadzali's inheritance law has its own value, namely by teaching the principle of equality as the division of men is twice as large as women is no longer relevant. He also did not explain the division of inheritors who have an upward line adequately. This is because Sjadzali only sees from the side of the historicity of the region as the birth of his 1: 1 inheritance concept, without regard to other aspects such as heirs and heirs.